2005
DOI: 10.1299/jsmec.48.570
|View full text |Cite
|
Sign up to set email alerts
|

A 3D Kinematic Measurement of Knee Prosthesis Using X-ray Projection Images(Countermeasure to the Overlap between the Tibial and Femoral Silhouettes)

Abstract: We have developed a technique for estimating 3D motion of knee prosthesis from its 2D perspective projections. As Fourier descriptors were used for compact representation of library templates and contours extracted from the prosthetic X-ray images, the entire silhouette contour of each prosthetic component was required. This caused such a problem as our algorithm did not function when the silhouettes of tibio and femoral components overlapped with each other. Here we planned a novel method to overcome it; whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Hirokawa et al [4] attempted to fit the overlapped outlines and reported poorer RSA results than other studies, which removed the overlapped outlines. The current authors attribute this to the fact that in Hirokawa's method, only the continuity of the outline curvatures is considered in the vicinity of the intersected points.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hirokawa et al [4] attempted to fit the overlapped outlines and reported poorer RSA results than other studies, which removed the overlapped outlines. The current authors attribute this to the fact that in Hirokawa's method, only the continuity of the outline curvatures is considered in the vicinity of the intersected points.…”
Section: Discussionmentioning
confidence: 99%
“…If the projected images of femoral and tibial prostheses are overlapped with each other, it is more difficult for the clinician to evaluate the prosthetic misalignment and wear (Fig. 1b) [4,6,9,12,13,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the details of the technique have been fully described elsewhere [9], a brief explanation will be given below.…”
Section: Countermeasure To the Overlapping Between The Tibial And Femmentioning
confidence: 99%
“…Although several researchers [3,9,22] have noted that displacement of the knee prosthesis components along the medico-lateral (z) axis is unlikely, the errors in z-translation result in errors of other kinds of rotation/translation. Then it was verified that incorporation of the articulation model improved estimation accuracies well, especially as for z-translation estimation accuracy to a remarkable extent (Fig.…”
Section: Incorporating the Articulation Modelmentioning
confidence: 99%